Nonlinear Elastic Waves for Evaluation of Composite Material Deterioration - LAMMERING, Rolf; RAUTER, Natalie (Engineering Transactions, 2016)
This work deals with numerical investigations on nonlinear wave propagation in order to detect micro-damage in composite material. For this purpose two models are under consideration. First, a wave guide with linear-elastic material behavior with and without a crack is analyzed. The nonlinearity of this model is due to the strain tensor as well as the contact of the crack surfaces. Secondly, a hyper-elastic waveguide with a nonlinear constitutive description is considered. It is shown, that the nonlinearity gives rise to second harmonic wave modes which which may be considered as an indicator of micro-damage and material deterioration.